2022
DOI: 10.1038/s41467-022-31220-8
|View full text |Cite|
|
Sign up to set email alerts
|

Wiskott-Aldrich syndrome protein forms nuclear condensates and regulates alternative splicing

Abstract: The diverse functions of WASP, the deficiency of which causes Wiskott-Aldrich syndrome (WAS), remain poorly defined. We generated three isogenic WAS models using patient induced pluripotent stem cells and genome editing. These models recapitulated WAS phenotypes and revealed that WASP deficiency causes an upregulation of numerous RNA splicing factors and widespread altered splicing. Loss of WASP binding to splicing factor gene promoters frequently leads to aberrant epigenetic activation. WASP interacts with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“… 137 Moreover, the condensates formed by WASP, SRSF2, RNA, and Pol II are able to control RNA transcription and splicing, and defects in condensate formation lead to Wiskott‐Aldrich syndrome. 184 …”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
See 2 more Smart Citations
“… 137 Moreover, the condensates formed by WASP, SRSF2, RNA, and Pol II are able to control RNA transcription and splicing, and defects in condensate formation lead to Wiskott‐Aldrich syndrome. 184 …”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
“…The condensates of STING were able to constrained TBK1 to prevent excessive activation of innate immunity, while microtubule inhibitors could hinder the generation of these condensates and increase the production of type I interferon in DNA virus‐infected cells 137 . Moreover, the condensates formed by WASP, SRSF2, RNA, and Pol II are able to control RNA transcription and splicing, and defects in condensate formation lead to Wiskott‐Aldrich syndrome 184 …”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wiskott-Aldrich Syndrome (WAS) is a severe X-linked PID caused by mutations in the WAS gene which encodes the WAS protein (WASp), a key regulator of cytoskeleton reorganization also involved in signaling transduction in all hematopoietic cells [193] . Recently, WASp roles in the nucleus have been described [194] , [195] , [196] , highlighting its multifaceted roles and explaining the complexity of clinical manifestations. The absence of WASp impairs both innate and adaptive immunity as well as platelet number and function resulting in the full-blown WAS characterized by immunodeficiency, thrombocytopenia, eczema and increased risk of autoimmune manifestations and malignancies [197] .…”
Section: Viral Mediated Gene Addition and Gene Editing Approaches For...mentioning
confidence: 99%
“…This suggests that WASP has other roles beyond regulating actin nucleation. Studies from our group and others have demonstrated the WASP functions in multiple biological processes , including regulating message RNA (mRNA) alternative splicing 5 , maintaining genome stability 6,7,8 , nuclear translocation of NFAT2 and NF-κB (RelA) 9 , and TH1 lineage commitment 10 .…”
Section: Introductionmentioning
confidence: 99%